A Comparative Study of Medical Records Management Efficiency Before and After the Implementation of the Sijiwa SIMRS at the HB Saanin Mental Hospital in Padang - Yuli Mardi; Nila Mayasari; Nofryanty, Nofryanty; Siti Rahmadani (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Digital transformation has become a crucial pillar in improving the quality of healthcare services globally. The Hospital Management Information System (SIMRS) has become a key requirement in improving the efficiency of administration and medical services, one of which is implemented at the HB. Saanin Mental Hospital through the Sijiwa SIMRS to overcome the constraints of manual medical record management. This study aims to evaluate the extent to which the implementation of the Sijiwa SIMRS improves the efficiency of medical record management. The methods used are quantitative and qualitative with a comparative approach through document analysis, surveys, and interviews, with data analysis in the form of descriptive statistics, Paired Sample T-Test, and thematic analysis. The results of the study indicate an increase in efficiency, including a reduction in patient registration time from 6 minutes 35 seconds to 5 minutes 2 seconds, file search time from 1 minute 18 seconds to 29 seconds, the number of staff reduced from 4 to 2 people while still being able to serve hundreds of patients, and file availability increased from 85% to 100%. Data input errors decreased from 10 to 1 document, although diagnostic coding errors were still found in 3–4 documents. Respondents expressed satisfaction because the system speeds up work and minimizes errors, but challenges such as network disruptions and feature limitations remain. This study recommends improving infrastructure and human resource competencies to optimize and enhance the benefits of SIMRS.